(untitled) (Quinto Sol, 2024)
The work recovers a series of interventions developed by the journalist and cultural producer Miguel Grinberg between 1980 and 1988, aimed at consolidating a memory of the Argentine and global counterculture in its original version. From this reconstruction, a series of problems related to the complexity of the hitherto naturalized link between counterculture and youth, and to the definition of a first “sixties” generational identity on the scale of Argentina are analyzed. Likewise, the particularities that countercultural narratives acquired as a modality of processing the recent Argentine past in the context of the so-called “transition” to democracy are addressed.